The Improving Of Condom Use In The Customers Of Prostitutes For HIV/ AIDS Prevention Through Peer Education At Gang Sadar Baturraden Localization Banyumas Regency 2013 - Suparmi Suparmi; Rusmini Rusmini; Ulfah Musdalifah (Jurnal LINK, 2014)
AIDS is a dangerous disease and can be transmitted easily by changing sexual partners. The Banyumas AIDS Commission reported in 2012 that 1,071 people suffered HIV/AIDS, including 715 people who suffered HIV and 256 people with AIDS. Among this number, 142 of them were died and 70 cases (35 %) were prostitutes. AIDS transmission can be prevented by using a condom during intercourse. Based on information from the Board Baturaden Tourism Society (PMPB), the proportion in condom use at Gang Sadar localized was 30 %. The aim of the study was to determine the increasing of condom use among prostitutes' customers for preventing HIV/ AIDS through peer education in the localization of Gang Sadar Baturaden Banyumas regency in 2013. The type of research used in the study was pre-experimental research with pretest - posttest design. The sample was 77 prostitutes at Gang Sadar Baturaden Banyumas. Paired t – test was used for data analysis. The results of the study showed that mean difference in condom use among customers of prostitutes before and after attending the peer education was 6 (z = -2.111, p=0.035). In conclusion, there was an increase in the consistency of condom use from 7 respondents (9.1 %) before giving the peer education to 14 respondents (18.2 %) after giving the peer education. The Advice for health workers and caregivers should constantly motivate and remind prostitutes as well as their customers to use a condom every time of their sexual intercourse.